1999
DOI: 10.1161/01.cir.100.suppl_2.ii-114
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Left Anterior Descending Coronary Artery Disease : Percutaneous Transluminal Coronary Angioplasty Versus Stenting Versus Left Internal Mammary Artery Bypass Grafting

Abstract: Background-Single-vessel coronary artery disease is usually treated with PTCA; however, this approach when applied to the left anterior descending coronary artery (LAD) is hampered by high restenosis rates, often approaching 50%. Coronary stenting (STENT) and left internal mammary artery bypass grafting of the LAD (LIMA-LAD) are other options that have been successfully used for single-vessel LAD disease. The optimal mode of revascularization for patients with isolated single-vessel LAD disease is unclear. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 22 publications
3
29
1
1
Order By: Relevance
“…[17][18][19] This trial showed MACE rates of 9.8% for all LAD lesions and 10.4% for proximal LAD lesions despite binary restenosis rates of 2% and 0%, respectively. This discrepancy has been shown in other drug-eluting stent trials as well.…”
Section: Sawhney Et Al Lad Pci With Sirolimus-eluting Stents 377mentioning
confidence: 87%
“…[17][18][19] This trial showed MACE rates of 9.8% for all LAD lesions and 10.4% for proximal LAD lesions despite binary restenosis rates of 2% and 0%, respectively. This discrepancy has been shown in other drug-eluting stent trials as well.…”
Section: Sawhney Et Al Lad Pci With Sirolimus-eluting Stents 377mentioning
confidence: 87%
“…1,2 Minimally invasive direct coronary artery bypass surgery and percutaneous coronary intervention with bare-metal stents are established treatment options that effectively relieve symptoms. 3,4 In randomized trials comparing the 2 strategies, a significantly higher reintervention rate after stenting and similar results for mortality and reinfarction at a 6-month follow-up have been demonstrated. 4 -6 Because the high initial success rate is eroded over time by clinical events, the long-term follow-up is more appropriate to elucidate the merits of surgery or the interventional procedure.…”
mentioning
confidence: 79%
“…Estudos prévios comparando angioplastia com cateter-balão ao tratamento cirúrgico com uso de enxertos arteriais no território da artéria DA demonstraram inferioridade da abordagem percutânea pela maior necessidade de reintervenção na lesão-alvo entre os pacientes tratados percutaneamente [13][14][15] . Ainda assim, as taxas de mortalidade eram comparáveis entre os dois grupos.…”
Section: Discussionunclassified